Bleeding Complications in Acute Coronary Syndromes and Percutaneous Coronary Intervention: Predictors, Prognostic Significance, and Paradigms for Reducing Risk - Manoukian, Steven V. (Clin Cardiol, 2007)
In clinical trials up to 30% of patients with acute coronary syndromes (ACS) or undergoing percutaneous coronary intervention (PCI) experience bleeding complications, and even higher rates have been reported in contemporary practice. A growing body of data suggests a strong correlation between bleeding and both short‐ and long‐term adverse outcomes, including mortality, which is independent of baseline characteristics and remains evident in most trials, despite variations in the definition of major bleeding. Although the value of antithrombin and antiplatelet therapy in reducing the risk of ischemic events is well established, the mechanisms of action that confer the benefits of these therapies have an inherent tendency to increase the risk of bleeding complications. As a result, characterization of baseline hemorrhagic risk is critical and must be accomplished before selecting an antithrombotic therapy. Risk factors for bleeding may be divided into two categories: nonmodifiable (including age, gender, race, weight, renal insufficiency, anemia, and acuity of presentation) and modifiable (including choice of antithrombotic therapy and PCI procedural characteristics). Of these predictive factors, the choice, dosage, and duration of the antithrombin and/or antiplatelet regimen are perhaps the most readily modifiable, especially in patients with an increased risk of bleeding. This review explores the nature of the association between bleeding and adverse outcomes, including mortality; evaluates risk factors for bleeding; and examines mechanisms for reducing bleeding complications through the selection of appropriate antithrombotic therapy. Copyright © 2007 Wiley Periodicals, Inc.